CHARACTERISTICS OF LIMESTONES FROM THE CIBODAS FORMATION AND CIKARANG MEMBER OF JAMPANG FORMATION IN CIKANGKUNG AREA, SUKABUMI REGENCY, WEST JAVA - Maulana, Muhammad Hafidz; Pratiwi, Santi Dwi (Fakultas Teknik Geologi Universitas Padjadjaran, 2024)
This research aims to identify the lithological characteristics as well as the occurrence of larger benthic foraminifera in limestone from the Cikangkung and surrounding area, Sukabumi Regency with coordinates between 106°25'40.707